Comparison of a Novel Bisphosphonate Prodrug and Zoledronic Acid in the Induction of Cytotoxicity in Human Vγ2Vδ2 T Cells - Okuno, Daisuke; Sugiura, Yuki; Sakamoto, Noriho; Tagod, Mohammed S. O.; Iwasaki, Masashi; Noda, Shuto; Tamura, Akihiro; Senju, Hiroaki; Umeyama, Yasuhiro; Yamaguchi, Hiroyuki; Suematsu, Makoto; Morita, Craig T.; et al. (Frontiers in Immunology, 2020)
Increasing attention has been paid to human γδ T cells expressing Vγ2Vδ2 T cell receptor (also termed Vγ9Vδ2) in the field of cancer immunotherapy. We have previously demonstrated that a newly synthesized tetrakis-pivaloyloxymethyl 2-(thiazole-2-ylamino)ethylidene-1,1-bisphosphonate (PTA) efficiently expanded peripheral blood Vγ2Vδ2 T cells to purities up to 95% - 99% in 10 to 11 days. In the present study, we first examined the effect of PTA on farnesyl diphosphate synthase (FDPS) using liquid chromatography mass spectrometry (LC-MS) to analyze the mechanism underlying the PTA-mediated expansion of Vγ2Vδ2 T cells and demonstrated that the prodrug induced the accumulation of both isopentenyl diphosphate (IPP) and dimethylallyl diphosphate (DMAPP), direct upstream metabolites of FDPS. This indicates that not only IPP but also DMAPP plays an important role in PTA-mediated stimulation of Vγ2Vδ2 T cells. We next analyzed TCR-independent cytotoxicity of Vγ2Vδ2 T cells. When human lung cancer cell lines were challenged by Vγ2Vδ2 T cells, no detectable cytotoxicity was observed in 40 min. The lung cell lines were, however, significantly killed by Vγ2Vδ2 T cells after 4 h to 16 h in an effector-to-target ratio-dependent manner, demonstrating that Vγ2Vδ2 T cell-based cell therapy required a large number of cells and longer time when tumor cells were not sensitized. By contrast, pulsing tumor cell lines with 10 - 30 nM of PTA induced significant lysis of tumor cells by Vγ2Vδ2 T cells even in 40 min. Similar levels of cytotoxicity was elicited by ZOL at concentrations of 100 - 300 M, which were much higher than blood levels of ZOL after infusion (1 - 2 μM), suggesting that standard 4 mg infusion of ZOL was not enough to sensitize lung cancer cells in clinical settings. In addition, Vγ2Vδ2 T cells secreted interferon-γ (IFN-γ) when challenged by lung cancer cell lines pulsed with PTA in a dose-dependent manner. Taken together, PTA could be utilized for both expansion of Vγ2Vδ2 T cells ex vivo and sensitization of tumor cells in vivo in Vγ2Vδ2 T cell-based cancer immunotherapy, although further studies on drug delivery are essential because of the hydrophobic nature of the prodrug.